Analysis of SARS-CoV-2 Spike Protein as The Key Target in the Development of Antiviral Candidates for COVID-19 through Computational Study - Taufik Muhammad Fakih; Mentari Luthfika Dewi (Journal of Tropical Pharmacy and Chemistry, 2021)
The recent public health crisis is threatening the world with the emergence of the spread of the new coronavirus 2019 (2019-nCoV) or severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This virus originates from bats and is transmitted to humans through unknown intermediate animals in Wuhan, China in December 2019. Advances in technology have opened opportunities to find candidates for natural compounds capable of preventing and controlling COVID-19 infection through inhibition of spike proteins of SARS-CoV-2. This research aims to identify, evaluate, and explore the structure of spike protein macromolecules from three coronaviruses (SARS-CoV, MERS-CoV, and SARS-CoV-2) and their effects on Angiotensin-Converting Enzyme 2 (ACE-2) using computational studies. Based on the identification of the three spike protein macromolecules, it was found that there was a similarity between the active binding sites of ACE-2. These observations were then confirmed using a protein-docking simulation to observe the interaction of the protein spike to the active site of ACE-2. SARS-COV-2 spike protein has the strongest bond to ACE-2, with an ACE score of ?1341.85 kJ/mol. Therefore, some of this information from the results of this research can be used as a reference in the development of competitive inhibitor candidates for SARS-CoV-2 spike proteins for the treatment of COVID-19 infectious diseases.